Prospect of Floriculture on Socio-Economic Condition Of Farmers in Gadkhali, Jashore, Bangladesh - Shaibur, MR; Husain, H; Akter, A (Bangladesh Journal of Agricultural Research, 2022)
Abstract not available Bangladesh J. Agril. Res. 45(1): 77-87, March 2020